The Exposure of Mortgage Borrowers to Interest Rate Risk and House Price Risk – Evidence from Swiss Loan Application Data - Martin Brown; Benjamin Suman Guin (Swiss Journal of Economics and Statistics, 2015)
We study the exposure of mortgage borrowers in Switzerland to interest rate and house price risks and examine how the households' choice of risky mortgages is related to individual interest rate expectations and risk-aversion. Our analysis is based on a unique data set of household mortgage applications from September 2012 until January 2014. Our assessment of risk exposure among mortgage borrowers in Switzerland is highly sensitive to the underlying assumptions on mortgage costs, household income and house value. Our main results suggest that the exposure of mortgage borrowers to interest rate and house price risks is limited in the medium term. We further document that the choice of mortgage contract seems to be more influenced by affordability concerns than risk concerns. In particular, individual interest rate expectations hardly affect mortgage contract choice.
Keywords: G21; D14; R21; R31; 330; mortgage default; mortgage choice; household finance; mortgage risk